2010
DOI: 10.1002/ppul.21378
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal measures of lung function in infants with bronchopulmonary dysplasia

Abstract: SUMMARY We previously demonstrated that infants with a history of bronchopulmonary dysplasia (BPD) exhibit airflow obstruction and air trapping. The purpose of this study was to assess longitudinal changes in pulmonary function in infants with a history of BPD over the first three years of life, and the relationship to somatic growth. Spirometry was measured using the raised volume rapid thoracoabdominal compression technique, and lung volumes measured by plethysmography. Eighteen infants (mean gestational age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 36 publications
5
59
1
5
Order By: Relevance
“…Seventeen papers were identified that evaluated pulmonary outcomes of preterm infants within the first 5 years of life (21,26,27,30,31,33,40,46,47,51,55,58,61,64,65,73,74). Varying definitions of BPD were used in these studies, with some defining BPD as persistent oxygen use at 28 days of age and others defining BPD based on an assessment at 36 weeks postmenstrual age.…”
Section: First 5 Years Of Lifementioning
confidence: 99%
“…Seventeen papers were identified that evaluated pulmonary outcomes of preterm infants within the first 5 years of life (21,26,27,30,31,33,40,46,47,51,55,58,61,64,65,73,74). Varying definitions of BPD were used in these studies, with some defining BPD as persistent oxygen use at 28 days of age and others defining BPD based on an assessment at 36 weeks postmenstrual age.…”
Section: First 5 Years Of Lifementioning
confidence: 99%
“…Of the 22 articles included (table 1), 12 assessed children with a history of BPD at different moments (longitudinal) [7][8][9][10][11][12][13][14][15][16]27,28 and the maximum follow-up was the interval between the neonatal hospital stay and five years of life. The remaining ten reviewed studies performed pulmonary function testing in one single moment (transversal).…”
Section: Resultsmentioning
confidence: 99%
“…However, these alterations may not be significant considering the normal values of pulmonary function parameters 12,17 . In this context, some authors 7,8,10 point out that improved pulmonary function during infancy is more evident in children with moderate/severe BPD, compared to those with mild BPD, or in preterm infants without BPD 28 . It is well-established that some complications caused by BPD in early childhood may favor high rates of respiratory infections, recurrent wheezing and hospital readmissions 12,28,33,34,36 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations